2020
DOI: 10.1007/s00018-020-03609-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal lineages derived from the nerve-associated Schwann cell precursors

Abstract: For a long time, neurogenic placodes and migratory neural crest cells were considered the immediate sources building neurons of peripheral nervous system. Recently, a number of discoveries revealed the existence of another progenitor type-a nerve-associated multipotent Schwann cell precursors (SCPs) building enteric and parasympathetic neurons as well as neuroendocrine chromaffin cells. SCPs are neural crest-derived and are similar to the crest cells by their markers and differentiation potential. Such similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 121 publications
(164 reference statements)
0
13
0
Order By: Relevance
“…differentiated states are under active maintenance by local signals. Under this view, we can consider that SCPs, which have been shown to be multipotent NCSCs [86,88,[152][153][154], and other NCSCs are NC-HMPs that have a histological and molecular phenotype driven by the local niche (e.g., for SCP, including the neuronal axon; [87]); consistent with this, the transcriptomic signature of SCPs and NCCs in mice are remarkably similar [38]. Release from that niche (e.g., when SCPs disperse from the axons; [86]) results in a change in the GRN state so that the NC-HMP resumes its fate sub-state cycling mode; this might be a key aspect of stem cell activation.…”
Section: When Does Commitment Occur?mentioning
confidence: 99%
“…differentiated states are under active maintenance by local signals. Under this view, we can consider that SCPs, which have been shown to be multipotent NCSCs [86,88,[152][153][154], and other NCSCs are NC-HMPs that have a histological and molecular phenotype driven by the local niche (e.g., for SCP, including the neuronal axon; [87]); consistent with this, the transcriptomic signature of SCPs and NCCs in mice are remarkably similar [38]. Release from that niche (e.g., when SCPs disperse from the axons; [86]) results in a change in the GRN state so that the NC-HMP resumes its fate sub-state cycling mode; this might be a key aspect of stem cell activation.…”
Section: When Does Commitment Occur?mentioning
confidence: 99%
“…17,18 Furthermore, previous reports revealed that Schwann cell precursors (SCPs) during embryonic development harbor NC cell features and are able to generate a variety of neural and non-neural cell types. 15,16 Likewise, carcinogenic lesions of adult NC-derived tissues such as melanoma or neuroblastoma can both present with cells expressing NCSC-associated factors that are not normally expressed in the healthy adult tissue. [19][20][21] This review focuses on melanoma, wherein the aberrant regulation or expression of developmental NCSC genes or pathways is associated with different aspects of malignancy (Figure 1), such as tumor initiation and sustained tumor growth, [22][23][24][25] promotion of metastatic spread, 26 as well as resistance to therapies [27][28][29][30] and immune evasion.…”
Section: Introductionmentioning
confidence: 99%
“…Injury‐activated glial cells were further shown to crucially assist regeneration of full‐thickness skin wounds or amputated digit tips 17,18 . Furthermore, previous reports revealed that Schwann cell precursors (SCPs) during embryonic development harbor NC cell features and are able to generate a variety of neural and non‐neural cell types 15,16 . Likewise, carcinogenic lesions of adult NC‐derived tissues such as melanoma or neuroblastoma can both present with cells expressing NCSC‐associated factors that are not normally expressed in the healthy adult tissue 19‐21 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the cells that make up the PNS, such as neurons and Schwann cells (SC), originate from the multipotent [ 8 ] neural crest (NC) cells. In fact, all glial cells of the PNS are of NC origin [ 9 , 10 ], while peripheral neurons stem from neurogenic placodes (non-NC origin), migrating NC cells, or later from Schwann cell precursors (SCP) [ 11 , 12 ]. Similarly, most of the major PNS nerves that innervate the digestive system are of NC origin, except for some cranial nerves (e.g., trigeminal and vagal nerves), which contain neurons of both placodal and NC origin [ 11 ].…”
Section: Origins Of the Pns Glial Cell Types And Their Functionsmentioning
confidence: 99%
“…It is proposed that the formation of NC-derived PNS neurons occurs in two waves. Initially, the short-lived multipotent migrating NC cells directly give rise to sensory and sympathetic neurons that have ganglia close to the spinal cord, whereas parasympathetic neurons, which reside in the distant ganglia closer to the target organs, arise from the SCPs migrating along the established preganglionic nerves [ 12 ]. Interestingly, the formation of the sacral autonomic outflow, which is generally considered parasympathetic, does not fit this model, since neurons of the pelvic ganglia can form even in the absence of the preganglionic neurons [ 13 ].…”
Section: Origins Of the Pns Glial Cell Types And Their Functionsmentioning
confidence: 99%